Keratinocytic Verrucous Epidermal Nevi in a Child - Shivani Deepak Jangid; Bhushan Madke (Journal of Clinical and Diagnostic Research, 2024)
A four-year-old male child was brought by the parents to the Dermatology Outpatient Department (OPD) with the complaint of a unilateral asymptomatic dark-coloured lesion over the right-side of the trunk, back, and upper limb since birth. The parents reported that the lesions increased in size proportionate to body growth, and the surface has become darker brown and rough. The child had age-appropriate weight and height and no history of neuro-developmental delay. Examination revealed large, dark brown, warty plaques in a linear pattern, strictly confined to the right half of the trunk and right upper limb. Two plaques (A and C) were seen to be extending from the anterior midline to the posterior midline [Table/Fig-1]. The other two plaques (B and D) were limited to only the posterior part of the right half of the trunk [Table/Fig-2].